The Malvaceae Collection at the Rio de Janeiro Botanical Garden: Ex Situ Conservation to Meet Target 8 of the Global Strategy for Plant Conservation - Carlos Daniel Miranda Ferreira; Juliana Ribeiro de Mattos; Marcus Alberto Nadruz Coelho; Massimo G. Bovini (Journal of Zoological and Botanical Gardens)
Ex situ conservation of plants is a current and urgent issue, especially in the Brazilian context. While Brazil has the world’s highest plant diversity, few consistent initiatives are aimed at conserving the potential of our living collections toward reaching Target 8 of the Global Strategy for Plant Conservation (GSPC). Objective II of GSPC calls for the conservation of plant diversity, with Target 8 specifying 75% of threatened plant species in ex situ collections. It was only after cataloging the collection of Malvaceae from the Rio de Janeiro Botanical Garden (JBRJ) for scientific publication that we realized the potential of this collection for ex situ conservation. With this in mind, we carefully catalog the individuals present, updating the names of species and counting their individuals. We found that Malvaceae is represented by 63 species and 216 individuals in the arboretum, 45 species native to America, 11 from Africa, 10 from Asia, and 3 from Oceania. Using IUCN criteria, only two species are threatened and two are data-deficient, with one or two individuals each. Based on these data and the specific biology of this taxonomic group, we identified the main problems and listed recommendations to make this collection more representative of the endangered taxa of the Brazilian flora. Therefore, we expect this effort to be a solid contribution to Target 8 mandated by GSPC, as well as a replicable pilot project for other taxonomic groups of Brazilian flora.